The Effect Of Public Service And E-Service Quality On Public Satisfaction At The Kerinci District Samsat Office - M Dhany Al Sunah; Afrianti; Nurfitri; Edwin Bustami; Arieska (International Humanity Advance, Business & Sciences, 2026)
This research was conducted at the Kerinci Regency Samsat Office. This study aimed to determine the effect of public service and e-service quality on public satisfaction. A sample size of 32 was selected using quantitative methods. Public service and e-service quality served as the independent variables, while public satisfaction served as the dependent variable. Multiple linear regression analysis (MLS) was used, including t-tests and F-tests, as well as hypothesis testing. The results of the multiple linear regression analysis revealed that public service influenced public satisfaction by 0.470 (47.0%), and e-service quality influenced public satisfaction by 0.563 (56.3%). The results of both partial and simultaneous hypothesis testing indicate that the independent variables significantly influence the dependent variable, based on the t-test. The regression results show that the calculated T value for each variable is Public Service = 3.997 and E-service Quality = 4.436. When compared with the predetermined significance level of α = 0.05 (Ttable = 1.697), the calculated T value is greater than the T value. Thus, Ho is rejected and Ha is accepted, meaning that Public Service and E-service Quality have a partially significant effect. Based on the F-test, the regression results show a significant value of 0.000 (<0.05). Based on the F-test results, the independent variables jointly exert a significant influence on the dependent variable. Therefore, it can be interpreted that Public Service and E-service Quality jointly have a significant effect on Public Satisfaction at the Kerinci Regency SAMSAT Office.